Pengaruh Pemberdayaan SDM, Budaya Organisasi, Dan Desain Kerja Terhadap Kinerja Karyawan Pada Lembaga Pendidikan Di Indonesia - Roselina Ramadhini Hasby; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to study the influence of empowerment, organizational culture, and work design on employee performance in educational institutions in Indonesia. This research uses a quantitative approach with a questionnaire distribution method. The sample for this research was 100 employees based on pre-research results. Data was obtained by distributing questionnaires and analyzed using descriptive statistics and path analysis in inferential statistics. Human resources play an important role in carrying out activities in a company. In order for the company's goals to be achieved, employees are needed who work efficiently and effectively so as to provide good work results. Employees are the main asset of the company and have a strategic role within the company, namely as thinkers, planners and controllers of company activities. In order to achieve company goals, employees need motivation to work more diligently. The research results can be concluded that: HR empowerment has a direct effect on employee performance, organizational culture has a direct effect on employee performance, job design has a direct effect on employee performance, empowerment has a direct effect on job design, and organizational culture has a direct effect on job design. Therefore, to improve employee performance, welfare, organizational culture and job design must be improved.